Scientific Discourse of Lakes in Nepal - Bhuju, DR; Sharma, S; Jha, PK; Gaire, NP (Nepal Journal of Science and Technology, 2013)
Over 5,000 standing water bodies, including those <1 ha and spread in 74 districts of Nepal have been scanned on the topographic sheets (scale of 1:125,000). Majority of these lakes or ponds are either in the high altitudes (above 3,000 m) or in lowland Tarai (below 500 m). In a literature review we found over 163 research studies conducted since the first study of lakes in 1969 in Khumbu region, majority being at the initiative of national academia, their faculties and graduate students. However, a complete inventory of Nepal’s lakes is still lacking. Their characteristics and distinction from wetlands are also to be defined as the existing laws and rules do not protect lakes or ponds categorically, rather they are blanketed under wetlands and/or other river like water resources. Research observations have shown that acid depositions are the most likely source of pollution affecting high altitude lakes in the Himalayan regions during spring. Their value as religious sites has also caused anthropogenic alteration in nutrient concentrations and biological assemblages of the lake. Encroachment to the lakes/ponds is rampant to which the natural processes of sedimentation, alien species invasion or any kind of obliteration become supportive. Capacity building, knowledge generation and threat management are vital to protect these natural heritages from untimely demise. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 147-158 DOI: http://dx.doi.org/10.3126/njst.v13i2.7728